Beyond energy balance regulation: The underestimated role of adipose tissues in host defense against pathogens - Barthelemy, Johanna; Bogard, Gemma; Wolowczuk, Isabelle (Frontiers in Immunology, 2023)
Although the adipose tissue (AT) is a central metabolic organ in the regulation of whole-body energy homeostasis, it is also an important endocrine and immunological organ. As an endocrine organ, AT secretes a variety of bioactive peptides known as adipokines – some of which have inflammatory and immunoregulatory properties. As an immunological organ, AT contains a broad spectrum of innate and adaptive immune cells that have mostly been studied in the context of obesity. However, overwhelming evidence supports the notion that AT is a genuine immunological effector site, which contains all cell subsets required to induce and generate specific and effective immune responses against pathogens. Indeed, AT was reported to be an immune reservoir in the host’s response to infection, and a site of parasitic, bacterial and viral infections. In addition, besides AT’s immune cells, preadipocytes and adipocytes were shown to express innate immune receptors, and adipocytes were reported as antigen-presenting cells to regulate T-cell-mediated adaptive immunity. Here we review the current knowledge on the role of AT and AT’s immune system in host defense against pathogens. First, we will summarize the main characteristics of AT: type, distribution, function, and extraordinary plasticity. Second, we will describe the intimate contact AT has with lymph nodes and vessels, and AT immune cell composition. Finally, we will present a comprehensive and up-to-date overview of the current research on the contribution of AT to host defense against pathogens, including the respiratory viruses influenza and SARS-CoV-2.